Aspects of hole-burning and spectro-temporal holography in molecular doped solids (Review Article) - Jean-Pierre Galaup (Физика низких температур, 2006)
The persistent spectral hole-burning (PSHB) phenomenon is known since 1974. It is still an
important research area for the study of the intimacy of complex molecular systems in the solid
state, revealing high resolution spectra, photophysics, photochemistry and dynamics of molecular
doped amorphous media, organic as well as inorganic. From another point of view, PSHB allows
the engraving of any spectral structures in the inhomogeneous absorption band profile of molecular
doped amorphous hosts or ion doped crystals cooled down to liquid helium temperatures.
Therefore, a PSHB material is programmable in the spectral domain and consequently it can be
transformed in an optical processor capable to achieve user-defined optical functions. Some aspects
of both fields are illustrated in the present paper. Concerning the search of efficient PSHB
materials, the hole burning performances and the photophysics of polymer and xerogel based
systems are compared. The problem of high-temperature persistent spectral hole-burning materials
and the search for new frequency selective photosensitive systems for fast optical pulse processing
at 800 nm are considered. Regarding the points treated, inorganic hosts based on silicate xerogels
or porous glasses have shown the best results. Moreover, by combining inorganic and organic
capabilities or by grafting organic species to the host, hybrid xerogels have not yet revealed all
possibilities. Also, the interest of two-photon materials for engraving spectral features with
near-infrared or infrared light is developed. As an introduction to possible applications of PSHB
material, the basics of spectro-temporal holography are remembered and a demonstrative experiment
using a naphthalocyanine doped polymer film is described, proving that the temporal
aberration free re-compression of ultrashort light pulses is feasible, therefore opening a way for
applications in ultrashort light pulse shaping. Aspects for a comparison between cw hole-burning
and femtosecond spectro-temporal experiments are considered and perspectives for the coherent
control of light fields or photochemical processes are also evoked.